The Effectiveness Of The Marbel Educational Application In Supporting Emergent Literacy In Early Childhood - Anugrah Robiah Al Adawiyah; Nabilla Anatasya Fortuna (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2025)
This study aims to describe the implementation of the interactive educational application Marbel in supporting the development of emergent literacy in early childhood. Emergent literacy refers to the early stage of reading and writing development, including letter recognition, initial sound awareness, and simple word understanding. This research employed a quantitative approach using a pre-experimental design with a One Group Pretest–Posttest design. The participants were 15 children aged 5–6 years from Group B at TK Pertiwi. Research instruments consisted of an emergent literacy test administered before and after the intervention, as well as observation sheets used as supporting data. Data were analyzed using descriptive quantitative analysis by comparing the mean scores of the pretest and posttest. The results showed an increase in the average emergent literacy score from 17.7 in the pretest to 25 in the posttest. These findings indicate that the use of the interactive educational application Marbel supports the stimulation of children’s emergent literacy. Observations also revealed increased focus and engagement during learning activities, which were positioned as supporting findings. Therefore, Marbel can be considered an alternative learning medium to support emergent literacy development in early childhood education.